Experimental Investigation of Pipeline In-Service Welding Process - Amori, Karima E.; Hussain, Mohammad N.; Hilal, Hadeel B. (Journal of Petroleum Research and Studies, 2018)
Welding of pipeline in active operation (called in-service welding) is an advanced technique employed to repair pipelines to safe transmission of petroleum or gas. A thermal experimental study is accomplished on welding process of gas pipeline in this work. An experimental setup had been designed, manufactured and instrumented to estimate the method for repairing locally pipelines defects (such as cracks and holes wall surface) under the influence of internal pressure. Also the thermal history of welding process was investigated experimentally to three cases which are : traditional welding process with no fluid flows inside the test pipe, an in-service welding process considering air as the flowing fluid inside test pipe, and an in-service welding process considering the liquefied petroleum gas (LPG) as flowing fluid inside test pipe. Results show that direct deposition of welding metal on a through hole under the influence of internal pressure succeeded for flow rate less than (12lpm) and failed for flow equal or higher than (12lpm) in which a sleeve repair is considered. The calculations are followed by a separate thermal stress analysis based on the thermal history.